Review and retrofitted architectures to form reliable smart microgrid networks for urban buildings. Issue 6 (1st November 2015) - Pavan Kumar, Y.V.; Bhimasingu, Ravikumar
Abstract : Smart microgrid initiatives for recent urbanisation at power distribution level need an integrated and interoperable environment that can work collectively with local energy systems and utility grid. This is achieved through the design of an architecture by using contemporary information and communication technology. System architecture provides a common work process that span across all the critical subsystems of a building for better informed decisions with reduced human interventions. Two key aspects of architecture development are, the way of its presentation and network reliability. The architecture should be clear in its presentation for the understanding of various stakeholders and possess fault tolerant communication mechanisms to have high network reliability. Considering aforementioned aspects, this study presents review of state‐of‐the‐art architectures developed by IEEE‐1547, ISA‐95, National Institute of Standards and Technology, IEC‐61850 for smart microgrids formation and suggests retrofitted architectures to improve architecture clarity by presenting in a more lucid way and network reliability by the concept of redundant communication paths.